Dampak Sosiologi Digital Terhadap Perubahan Sosial Budaya Pada Masyarakat Masa Depan - Dahniar Nur; Nurfadilah Syawal Ibraya; Nur Riswandy Marsuki (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to explain the role and evolution of digital sociology. The development of digital technology has fundamentally changed the paradigm of social interaction and societal dynamics. Digital sociology has become a key instrument in understanding the impact of this transformation, focusing on the influence of the internet and social media on communication, interaction and social identity formation. Digital sociology not only reflects current realities, but also has major consequences for future changes. This research method is a literature study by collecting references from journal articles, books and social media news. Content analysis is used to understand the dynamics of communication and social change. The results of this research discuss the development of a more connected society, paying attention to the growth of social media users globally. Social and cultural changes that may occur as a result of digital sociology include transformations in communication, the influence of digital media, changes in work and the economy, popular culture, privacy, education, identity, and social activism. This research confirms that digital sociology is an integral element in understanding societal change in the digital era, guiding us in facing challenges and exploiting emerging opportunities.